Child Workers in Sabahattın Ali's Stories - Oruç, Osman (Fırat University, 2023)
After Ömer Seyfettin, who took the story as an independent genre independent of the novel and made this understanding accepted, Sabahattin Ali constitutes a breaking point in the history of Turkish short stories. Sabahattin Ali, without compromising the story, deals with the issues brought to the agenda by the socialist realist storytellers who clustered around the Vakit Newspaper in the 1930s, with a propagandist attitude. Child labor, which has always been a reality of Turkey, is also brought to the fore in some stories of Sabahattin Ali, a socialist realist artist. Sabahattin Ali, by processing the social injustice observed in social life through child workers, brings the aforementioned problem to the attention of the reader in a much stronger way, almost as a cry. In the three stories that are the subject of the study, the conflict between those who work hard with their small/weak bodies and consume less, and those who work hard or consume a lot with their fat/oversize bodies are handled. In this study, it will be focused on the reality of child workers forced to work by the corrupt order that emerged as a result of social injustice in Sabahattin Ali's stories 'Apartman', 'Arabalar Beş Kuruşa' and 'Ayran'.

Hikâyeyi romandan bağımsız ‘müstakil bir tür’ olarak alan ve bu anlayışı kabul ettiren Ömer Seyfettin’den sonra Türk hikâye tarihinde Sabahattin Ali bir kırılma noktası teşkil eder. 1930’lu yıllarda Vakit Gazetesi etrafında kümelenen toplumcu gerçekçi hikâyecilerin propagandist bir tavırla gündeme getirdikleri meseleleri Sabahattin Ali kuru ideolojiyi geri planda tutarak, hikâyeden taviz vermeden ele alır. Öteden beri bir Türkiye gerçeği olan çocuk işçiler toplumcu gerçekçi bir sanatçı olan Sabahattin Ali’nin kimi hikâyelerinde de gündeme getirilir. Sabahattin Ali, toplumsal hayatta gözlenen sosyal adaletsizliği çocuk işçiler vasıtasıyla işleyerek söz konusu sorunu çok daha güçlü bir biçimde, adeta bir çığlık halinde okuyucunun dikkatine sunar. Çalışmaya konu üç hikâyede küçük/çelimsiz bedenleriyle çok çalışıp az tüketenler ile semirmiş/haddinden fazla iri bedenleriyle az çalışıp yahut hiç çalışmayıp çok tüketenlerin çatışması işlenir. Bu çalışmada Sabahattin Ali’nin ‘Apartman’, ‘Arabalara Beş Kuruşa’ ve ‘Ayran’ adlı hikâyelerinde sosyal adaletsizliğin bir sonucu olarak ortaya çıkan bozuk düzenin çalışmaya ittiği çocuk işçiler gerçeği üzerinde durulacaktır.
SABAHATTİN ALİ’NİN HİKÂYELERİNDE ÇOCUK İŞÇİLER